The Oxford handbook of the Phoenician and Punic mediterranean - López-Ruiz, Carolina; Doak, Brian (Oxford handbooks, 2019)
The Phoenicians created the Mediterranean world as we know it--yet they remain a poorly understood group. In this Handbook, the first of its kind in English, readers will find expert essays covering the history, culture, and areas of settlement throughout the Phoenician and Punic world.